IL12-mediated sensitizing of T-cell receptor-dependent and -independent tumor cell killing. (2nd July 2016) - Braun, Matthias; Ress, Marie L.; Yoo, Young-Eun; Scholz, Claus J.; Eyrich, Matthias; Schlegel, Paul G.; Wölfl, Matthias
ABSTRACT: Interleukin 12 (IL12) is a key inflammatory cytokine critically influencing Th1/Tc1-T-cell responses at the time of initial antigen encounter. Therefore, it may be exploited for cancer immunotherapy. Here, we investigated how IL12, and other inflammatory cytokines, shape effector functions of human T-cells. Using a defined culture system, we followed the gradual differentiation and function of antigen-specific CD8 + T cells from their initial activation as naïve T cells through their expansion phase as early memory cells to full differentiation as clonally expanded effector T cells. The addition of IL12 8 days after the initial priming event initiated two mechanistically separate events: First, IL12 sensitized the T-cell receptor (TCR) for antigen-specific activation, leading to an approximately 10-fold increase in peptide sensitivity and, in consequence, enhanced tumor cell killing. Secondly, IL12 enabled TCR/HLA-independent activation and cytotoxicity: this "non-specific" effect was mediated by the NK cell receptor DNAM1 (CD226) and dependent on ligand expression of the target cells. This IL12 regulated, DNAM1-mediated killing is dependent on src-kinases as well as on PTPRC (CD45) activity. Thus, besides enhancing TCR-mediated activation, we here identified for the first time a second IL12 mediated mechanism leading to activation of a receptor-dependent killing pathway via DNAM1.